2020
DOI: 10.3847/1538-4357/abc345
|View full text |Cite
|
Sign up to set email alerts
|

PSR J1641+3627F: A Low-mass He White Dwarf Orbiting a Possible High-mass Neutron Star in the Globular Cluster M13

Abstract: We report on the discovery of the companion star to the millisecond pulsar J1631+3627F in the globular cluster M13. By means of a combination of optical and near-UV high-resolution observations obtained with the Hubble Space Telescope, we identified the counterpart at the radio source position. Its location in the color–magnitude diagrams reveals that the companion star is a faint ( ) He-core white dwarf. We compared the observed companion magnitu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 102 publications
0
15
0
Order By: Relevance
“…The photometric analysis was performed via the point-spread function (PSF) fitting method, by using DAOPHOT IV 27 and following the "UV-route" approach used in previous works [28][29][30][31][32][33][34] . Briefly, the photometric analysis was carried out on the "_flc" images (which are the UVIS calibrated exposures, including Charge Transfer Efficiency correction) and it consists in first searching for the stellar sources in the near-UV images, then force-fit the source detection at longer wavelengths at the same positions of the UV-selected stars.…”
Section: Methodsmentioning
confidence: 99%
“…The photometric analysis was performed via the point-spread function (PSF) fitting method, by using DAOPHOT IV 27 and following the "UV-route" approach used in previous works [28][29][30][31][32][33][34] . Briefly, the photometric analysis was carried out on the "_flc" images (which are the UVIS calibrated exposures, including Charge Transfer Efficiency correction) and it consists in first searching for the stellar sources in the near-UV images, then force-fit the source detection at longer wavelengths at the same positions of the UV-selected stars.…”
Section: Methodsmentioning
confidence: 99%
“…The photometric analysis was carried out on the _flc images (which are the UVIS calibrated frames, also corrected for charge transfer efficiency), after applying the Pixel Area Map (PAM) correction. We used DAOPHOT IV (Stetson 1987) to follow the so-called "UV-route," which consists of first searching for stellar sources in the near-UV images, then force-fitting the source detection at the same positions of the UV-selected stars in longer wavelength images (Ferraro et al 1997b(Ferraro et al , 2001(Ferraro et al , 2003Raso et al 2017;Dalessandro et al 2018bDalessandro et al , 2018aCadelano et al 2019Cadelano et al , 2020a. This procedure allows the optimal recovering of blue and faint objects, like WDs, because the crowding effect generated by giants and main-sequence turnoff (MS-TO) stars (which get brighter with increasing wavelengths) is strongly mitigated in near-UV images of old stellar populations (as Galactic GCs).…”
Section: Data Reductionmentioning
confidence: 99%
“…This pulsar was discovered in a 500-700 MHz subband of the single beam ultra wide band receiver covering 270-1620 MHz with an 0.5-hr observation. With the same receiver, Wang et al (2020) reported the FAST discovery of M13F, which might be an extremely faint and scintillating pulsar, lately shown to be a high-mass neutron star (Cadelano et al 2020); they also confirmed that M13E is a back widow system. More GC pulsar discoveries were done with the 19-beam L-band receiver which replaced the single beam ultra wide band receiver on May of 2018.…”
Section: Introductionmentioning
confidence: 88%